Short-Term Effects of Transitioning from Conventional to Electronic Cigarettes on Body Mass Index in Young Adult Males: A Prospective Cohort Study - Pribadi, Indra Mustika Setia; Sulastri, Afianti; Amaliya, Amaliya; Polosa, Riccardo (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Nicotine is known to influence appetite suppression and energy expenditure, potentially contributing to the lower body mass index (BMI) observed among smokers. However, the short-term metabolic impact of switching from combustible cigarettes to electronic cigarettes (e-cigarettes) remains uncertain. Objective: This study aimed to evaluate the effect of transitioning from conventional cigarettes to e-cigarettes on BMI among young adult male smokers over a three-month period. Method: A prospective cohort study was conducted involving 47 male smokers aged 20–40 years. Participants were allocated into two groups: those who switched to e-cigarettes (n = 30) and those who continued smoking conventional cigarettes (n = 17). BMI was assessed at baseline and after three months. Data were analyzed using paired and independent t-tests to evaluate intra- and intergroup differences. Result: In the e-cigarette group, BMI slightly declined from 24.16 ± 4.42 to 24.06 ± 4.59 kg/m² (Δ = –0.11 ± 0.63, p = 0.379), whereas in the conventional group, BMI increased marginally from 22.54 ± 3.63 to 22.63 ± 3.63 kg/m² (Δ = +0.09 ± 0.52, p = 0.486). The between-group difference in BMI change was not statistically significant (p = 0.289). Conclusion: Short-term transition to e-cigarette use did not result in significant changes in BMI among young adult male smokers. These findings suggest that e-cigarettes are metabolically neutral over short durations and should not be regarded as effective tools for weight control. Further longitudinal studies are warranted to explore longer-term metabolic outcomes.